Yearbook International Tribunal for the Law of the Sea / Annuaire Tribunal international du droit de la mer, Volume 28 (2024) (International Law E-books Online, Collection 2026., 2026)
The ITLOS Yearbook 2024 provides information on the composition and organization of the Tribunal and reports on its judicial activities in 2024, in particular concerning Cases Nos. 31 to 33. The Yearbook is prepared by the Registry of the Tribunal. Le TIDM Annuaire 2024 fournit des informations sur la composition et l'organisation du Tribunal et rend compte des activités judiciaires de celui-ci au cours de l'année 2024, en particulier en ce qui concerne les affaires nos. 31 à 33. L 'Annuaire est préparé par le Greffe du Tribunal.